The Cowboy Whisperer - Sol, Sabrina (New York : Forever, 2023)
After her last disastrous competition went viral, Olympic hopeful Veronica del Valle spent three years healing - and hiding. Finally ready for another shot, Veronica agrees to train at an under-the-radar, family-run ranch in tiny Esperanza, California. The living accommodations? Sparse. High-end equestrian equipment? Zero. What Rancho Lindo does have is stable manager Tomas Ortega, a brooding, handsome cowboy who offers Veronica unsolicited advice during her training sessions. Advice that, infuriatingly, turns out to be right every time. The only thing Tomas cares about are his horses and saving his familys ranch-- and not their new boarder, who makes it clear shes not happy with his stables. So hes shocked Veronica offers to pretend to be his girlfriend when Tomass ex comes back to town. All she wants in return is some after-hours training. He soon realizes Veronica is nothing like he imagined, and the harder he falls, the more he worries, because Veronicas Olympic dreams will eventually take her away from Rancho Lindo - and from him.
Keywords: Man-woman relationships -- Fiction; Ranchers -- Fiction; Runners (Sports) -- Fiction; Romance fiction; Western fiction